급속소결에 의한 나노구조 NiTi 합금의 제조 및 기계적 특성 - 김나리; Na Ri Kim; 고인용; In Yoong Ko; 조성욱; Sung Wook Cho; 김원백; Won Baek Kim; 손인진; In Jin Shon (대한금속·재료학회지, 48(9), 2010)
NiTi powders were synthesized during high energy ball milling for 10 h. Highly dense nanostructured NiTi with a relative density of up to 99% was obtained within 1 minute by high frequency induction heated sintering under a pressure of 80 MPa. The grain size, microstructure, and mechanical properties of NiTi were investigated. The grain size and hardness of TiNi are about 122 nm and 590 kg/mm2, respectively.